Control or destroy: Wildfire as a response mechanism - Ekberzade, Bikem; Görüm, Tolga (Copernicus GmbH, 2026)
The role of wildfire as a controller in wildland ecosystems is well researched. However, much uncertainty is present with climate change. Will this morphing force turn into a game breaker in the longevity of terrestrial ecosystems? Or will it continue its role as the ultimate controller of vegetation composition, and for certain taxa, fecundity? This study aims to answer these questions for a study region situated in the northern segment of Eastern Mediterranean Basin – Anatolian Peninsula and its immediate surroundings. It considers the historical and potential future changes in biomass and fuel capacity in the region with respect to the changes in amplitudes of climate variability due to climate change in two distinct time periods (present and future). Changes in fire severity and fire return interval (FRI) are simulated using a dynamic vegetation model (LPJ-GUESS v.4.1) coupled with wildfire modules (SIMFIRE and BLAZE), and high-resolution climate datasets. For 1961-2025, the model is forced with ERA5-Land reanalysis data, and for 1961-2100, an ensemble of 5 CMIP6 datasets under the SSP 5-8.5 global warming scenario are used which are resized to 0.1°. While the historical trend analyses of the climate indices (such as SPEI) indicate strong drying for the region overall, simulation results signal an increase in burned area, the frequency of wildfire incidents, while highlighting important changes in vegetation composition and biomass under a changing climate, as wildfire turns into a response mechanism under increasing temperatures and changing rainfall patterns.